Multi‐mode acquisition (MMA): An MS/MS acquisition strategy for maximizing selectivity, specificity and sensitivity of DIA product ion spectra. Issue 15 (August 2016) - Williams, Brad J.; Ciavarini, Steve J.; Devlin, Curt; Cohn, Steven M.; Xie, Rong; Vissers, Johannes P.C.; Martin, LeRoy B.; Caswell, Allen; Langridge, James I.; Geromanos, Scott J.
Abstract : In proteomics studies, it is generally accepted that depth of coverage and dynamic range is limited in data‐directed acquisitions. The serial nature of the method limits both sensitivity and the number of precursor ions that can be sampled. To that end, a number of data‐independent acquisition (DIA) strategies have been introduced with these methods, for the most part, immune to the sampling issue; nevertheless, some do have other limitations with respect to sensitivity. The major limitation with DIA approaches is interference, i.e., MS/MS spectra are highly chimeric and often incapable of being identified using conventional database search engines. Utilizing each available dimension of separation prior to ion detection, we present a new multi‐mode acquisition (MMA) strategy multiplexing both narrowband and wideband DIA acquisitions in a single analytical workflow. The iterative nature of the MMA workflow limits the adverse effects of interference with minimal loss in sensitivity. Qualitative identification can be performed by selected ion chromatograms or conventional database search strategies.